OPTIMIZATION OF THE CLINICAL METHODOLOGY OF SELECTIVE OCCLUSAL ADJUSTMENT IN PATIENTS WITH GENERALIZED PERIODONTITIS USING THE T-SCAN DIGITAL OCCLUSAL SYSTEM (American Journal of Pedagogical and Educational Research, 2026)
This article presents the scientific and theoretical foundations for optimizing the selective occlusal adjustment protocol in patients with generalized periodontitis using the T-Scan digital occlusal analysis system. The mechanisms for detecting hidden super contacts, objectively assessing masticatory load distribution, and reducing occlusion time to physiological values through digital monitoring are examined. The role of traumatic occlusion in the development of destructive processes in periodontal tissues is scientifically substantiated, along with the advantages of digital occlusal analysis over traditional diagnostic methods. Contemporary occlusal correction protocols, the principles of functional stability of the dentofacial system, and the significance of a comprehensive approach in the treatment of generalized periodontitis are analysed.